STRATEGI PEMASARAN IKAN NILA UNTUK KEBERLANJUTAN UNIT BISNIS PERIKANAN UNIVERSITAS MUHAMMADIYAH SIDENRENG RAPPANG - Bibin, Muhammad; Sulaeman, Muhammad Anugrah; Febrian, Muh. Rizal; Farhansyah R, Muh. (Universitas Muhammadiyah Gresik, 2025)
As a fishery commodity with high economic value, tilapia has great potential to be developed through a planned marketing approach. This study aims to analyze the development strategy of the Fisheries business unit at the University of Muhammadiyah Sidenreng Rappang. This study uses the purposive sampling method to select respondents from UMSR fisheries business unit managers, UMSR academics, and government agencies of Sidenreng Rappang Regency. The data was analyzed using SWOT analysis to identify internal (strengths and weaknesses) as well as external (opportunities and threats) faktors that affect business development. The results of the study show that the main strength of the business unit lies in the fact that the tilapia that is cultivated has excellent quality, due to the professional management system, while the significant weakness is the limitation of marketing networks and financial resources. The biggest opportunity is the support from the Sidenreng Rappang Regency government in the development of tilapia cultivation in the UMSR fishery business unit. However, fierce competition and raw material prices are the main threats. Recommended priority strategies include product diversification by processing tilapia into fillets, nuggets, or other value-added products. Strengthening branding through digital marketing to expand market reach and expand distribution networks through collaboration with major distributors and the use of e-commerce.